2015
DOI: 10.3389/fpls.2015.00707
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis approach for assessing the diversity and specificity of belowground root and microbial volatiles

Abstract: Volatile organic compounds are secondary metabolites emitted by all organisms, especially by plants and microbes. Their role as aboveground signals has been established for decades. Recent evidence suggests that they might have a non-negligible role belowground and might be involved in root–root and root–microbial/pest interactions. Our aim here was to make a comprehensive review of belowground volatile diversity using a meta-analysis approach. At first we synthesized current literature knowledge on plant root… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 75 publications
1
76
0
Order By: Relevance
“…Given that (1) VOCs play important ecological roles in plant-plant interactions aboveground, (2) plants can detect chemical signals emitted in the rhizosphere of their neighbours (roots and associated microorganisms), and (3) roots are able to synthesise and release VOCs in the soil (Table 1), questions arise relating to the ecological roles played by belowground VOCs in root-root interactions (Schenkel et al 2015). With regard to allelopathic interactions, plant VOCs are able to generate oxidative stress (Zunino and Zygadlo 2004;Singh et al 2006).…”
Section: Studying Voc-mediated Root-root Interactions: Challenges Andmentioning
confidence: 99%
“…Given that (1) VOCs play important ecological roles in plant-plant interactions aboveground, (2) plants can detect chemical signals emitted in the rhizosphere of their neighbours (roots and associated microorganisms), and (3) roots are able to synthesise and release VOCs in the soil (Table 1), questions arise relating to the ecological roles played by belowground VOCs in root-root interactions (Schenkel et al 2015). With regard to allelopathic interactions, plant VOCs are able to generate oxidative stress (Zunino and Zygadlo 2004;Singh et al 2006).…”
Section: Studying Voc-mediated Root-root Interactions: Challenges Andmentioning
confidence: 99%
“…The responses include a combination of priming and induced defences, according to the allocation cost of different classes of defence, with plants priming more expensive responses and inducing less costly metabolites, such as extrafloral nectar or HIPVs, to attract natural enemies of the herbivore Frost et al, 2008b). Participation of volatiles in interplant below-ground interactions is not well elucidated (Schenkel et al, 2015;Delory et al, 2016). Whether VOCs emitted by roots in the rhizosphere can diffuse into the phyllosphere and convey signals to prime above-ground parts of the same plant is also not effectively documented (Erb et al, 2008).…”
Section: Airborne Signalling To Neighbouring Plants and Systemic Partmentioning
confidence: 99%
“…Alcohols have widespread effects in plants (Piechulla et al, ), and they represent about 16% of the mVOCs diversity (Schenkel, Lemfack, Piechulla, & Splivallo, ). In this study, BA and PA were the most frequently found mVOCs, being present in more than 70% of the strains.…”
Section: Discussionmentioning
confidence: 99%